Zakon o zdravstvenem varstvu in zdravstvenem zavarovanju - Strban, Grega (Podjetje in delo, 2023)
Legal regulation of the compulsory health insurance has to follow the modified societal relations. It is of lesser importance whether this is done with a new legislative act or mere amendments to the existing one. The starting point is the Constitution of the Republic of Slovenia, based on international standards when regulating fundamental human rights to social security and to healthcare. All principles and rules of social insurance apply also to the compulsory health insurance. With regulation of a public scheme, intervention into the private market and all the pitfalls that come with it can be avoided. In the present paper, constitutional provisions and legal relations under the compulsory health insurance are analysed. It is established that updating all of them would be required, i.e. determining the scope of insured persons, funding, administration and, most of all, providing healthcare for the compulsory health insurance.
Keywords: obvezno zdravstveno zavarovanje; pravna ureditev; socialna varnost; socialno zavarovanje; Zdravstveno varstvo; Zdravstveno zavarovanje